The adverse effects of domestic violence on psychosocial well-being - Siltala, Heli (2014)
The purpose of this study was to investigate the effects of domestic violence on psychosocial well-being.Comparisons were made between the effects of psychological, physical and sexual abuse. Possible gender differences in the prevalence and effects of domestic violence were also taken into account. The data used in this study was collected from the staff of the Central Finland Health Care District in 2010. A total of 1 952 people participated in the study. The dependent variables included in this study were depressive symptoms, sleep quality and well-being as measured by both self-evaluation and MHC-SF questionnaire. The relationship between domestic violence and well-being was studied using crosstabs, regression analyses, variance analyses and mediator analyses. The results showed that 44 % of women and 24 % of men had experienced some kind of domestic violence. “Psychological abuse only” was the most common abuse group, followed by “psychological & physical abuse”. In all abuse groups, the number of women was significantly higher than that of men. Participants with domestic violence experiences scored significantly worse on all measures used in the study and this effect was strongest among those experiencing psychological abuse only. This result is compatible with previous research findings emphasizing the importance of psychological domestic violence. Findings from the mediation analyses suggest that these adverse effects of psychological abuse can at least partially be explained by decrease in sleep quality. The results also suggest that domestic violence might have different effects on women and men. These findings should be taken into account at the various services aimed at decreasing the adverse effects of domestic violence.